Pixel-wise tree cover productivity in the Arctic from 2000 - 2020 - Ludwig, Antonia; Heim, Birgit; Feilhauer, Hannes (PANGAEA, 2025)
With this raster dataset, we provide pixel-wise information on tree cover changes from 2000 to 2020 in the pan-arctic region at a spatial resolution of 15 km. The trends are provided in two metrics: (1) as pixel-wise Theil-Sen slopes that indicate the overall changes in tree cover across the given time span, and (2) as the integrated area under the curve which described the total tree cover present in a pixel across all time points. The calculations were based on an aggregated version of the already existing Arctic-boreal tree canopy cover dataset from Feng et al. (2022). The data for the pan-arctic region was retrieved from the official repository in 2.5° x 2.5° tiles at 30 m spatial resolution (https://doi.org/10.3334/ORNLDAAC/2012). The tiles were processed individually and finally merged to a user-friendly pan-arctic raster layer. Here, we provide two raster layers, one for each metric, that are ready to use in open-source GDAL applications, such as R or QGIS, for further exploration. They allow the identification of hot spots of tree cover productivity or serve as valuable input for vegetation and climate models.
Keywords: Arctic-Boreal; Change detection; Maps; raster layer; tree cover